2021
DOI: 10.3389/fonc.2021.559161
|View full text |Cite
|
Sign up to set email alerts
|

Combination Strategies to Augment Immune Check Point Inhibitors Efficacy - Implications for Translational Research

Abstract: Immune checkpoint inhibitor therapy has revolutionized the field of cancer immunotherapy. Even though it has shown a durable response in some solid tumors, several patients do not respond to these agents, irrespective of predictive biomarker (PD-L1, MSI, TMB) status. Multiple preclinical, as well as early-phase clinical studies are ongoing for combining immune checkpoint inhibitors with anti-cancer and/or non-anti-cancer drugs for beneficial therapeutic interactions. In this review, we discuss the mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 162 publications
1
31
0
Order By: Relevance
“…Other groups have corroborated our findings and reported other cancer cell-specific PD-1 activation of oncogenic signaling cascades [3,4,[6][7][8], which appear to be dependent on the cancer histology [4,6]. Building upon our body of work showing an oncogenic role for endogenous PD-1 expression in PDAC, we discovered that highly activated c-MET (MET, mesenchymal-epithelial transition factor) was regulated by PD-1/PD-L1 signaling in PDAC cells.…”
Section: Introductionsupporting
confidence: 89%
“…Other groups have corroborated our findings and reported other cancer cell-specific PD-1 activation of oncogenic signaling cascades [3,4,[6][7][8], which appear to be dependent on the cancer histology [4,6]. Building upon our body of work showing an oncogenic role for endogenous PD-1 expression in PDAC, we discovered that highly activated c-MET (MET, mesenchymal-epithelial transition factor) was regulated by PD-1/PD-L1 signaling in PDAC cells.…”
Section: Introductionsupporting
confidence: 89%
“…Preclinical and clinical trials have identified metabolic targeting drugs with the potential to enhance the efficacy of immune checkpoint blockade therapy [ 151 , 152 ]. The synergism of immune checkpoint blockade therapy combined with metformin against tumor burden has been demonstrated in preclinical studies [ 153 , 154 , 155 ].…”
Section: Clinical Perspective Of Immune Checkpoint Blockade Therapymentioning
confidence: 99%
“…Furthermore, it has been shown that the favorable immune effects mediated by BRAF/MEKi are paralleled by the induction of T cell exhaustion markers and, thus, treatment response appears to subside in the long-term [ 100 ]. Therefore, it has been proposed by a number of preclinical studies and clinical trials that the efficacy of ICI [ 106 ] and BRAFi/MEKi [ 19 , 107 ] may be considerably enhanced by co-administration of additional anti-tumor drugs (such as conventional chemo or radiotherapy), as well as agents which act on regulatory immune cells (i.e., antiangiogenic drugs, tyrosine kinase receptor antagonists).…”
Section: Conclusion/perspectivesmentioning
confidence: 99%